Immunomodulatory Effect of Bisphosphonate Risedronate Sodium on CD163+ Arginase 1+ M2 Macrophages: The Development of a Possible Supportive Therapy for Angiosarcoma - Taku Fujimura; Yumi Kambayashi; Sadanori Furudate; Aya Kakizaki; Setsuya Aiba (Clinical and Developmental Immunology)
An imbalance of immunosuppressive cells and cytotoxic cells plays an important role in inhibiting the antitumor immune response of the tumor-bearing host. We previously reported the profiles of tumor infiltrating leukocytes in cutaneous angiosarcoma (AS) and suggested that a combination of docetaxel (DTX) with bisphosphonate risedronate sodium (RS) might be effective for MMP9-expressing AS by targeting immunosuppressive cells such as M2 macrophages. To further confirm the effect of this combination therapy, in this report we investigated the immunomodulatory effect of DTX and RS on CD163+ arginase 1 (Arg1)+ M2 macrophages in vitro. Interestingly, our present study demonstrated that DTX in combination with RS significantly upregulated the mRNA expression of CXCL10 on M2 macrophages and significantly decreased the mRNA expression of CCL17 and Arg1. Moreover, the production of CXCL10 and CXCL11 from M2 macrophages was significantly increased by DTX with RS though there was no effect of DTX with RS on the production of CCL5 and CCL17. Furthermore, DTX with RS significantly decreased the production of CCL18, which was previously reported to correlate with the severity and prognosis in cancer patients. Our present report suggests one of the possible mechanisms of DTX with RS in the supportive therapy for angiosarcoma.